Initial assessment of the COMPASS/BeiDou-2 regional navigation satellite system - Montenbruck, O.; Hauschild, A.; Steigenberger, P.; Hugentobler, U.; Teunissen, Peter; Nakamura, S. (Springer, 2012)
An initial characterization and performance assessment of the COMPASS/BeiDou-2 regional navigation system is presented. Code and carrier phase measurements on up to three frequencies have been collected in March 2012 with a small regional network of monitoring stations. The signal and measurement quality are analysed and compared with the Japanese Quasi Zenith Satellite System. A high level of stability is demonstrated for the inter-frequency carrier phase biases, which will facilitate the application of triple-frequency undifferenced ambiguity resolution techniques in future precise point positioning applications. The performance of the onboard Rubidium frequency standards is evaluated in comparison to ground based hydrogen masers and shown to be well competitive with other GNSS satellite clocks. Precise orbit and clock solutions obtained in post-processing are used to study the presently achievable point positioning accuracy in COMPASS/BeiDou-2-only navigation. Finally, the benefit of triple-frequency measurements and extra-wide-lane ambiguity resolution is illustrated for relative positioning on a short baseline.